Estructuración del modelo de educación inclusiva: una propuesta de convergencia entre la asociación Fé y Alegría y el Ministerio de Educación para la inclusión a la educación regular de personas con discapacidad, durante el año 2012 - 2013. - Ramírez Morales, Gabriela Isabel (2013)
In the present study aims to improve the educational care of this group with special educational needs attended in Fe y Alegría Association in partnership with the Ministry of Education, as well as expanding health care coverage through an inclusive education model, a guide practice for teachers, parents and students.